Variabilidade espacial do estado nutricional do cafeeiro conilon utilizando índice DRIS - Fonseca, Abel Souza da (2014)
The objective of this study was to evaluate the spatial variability of nutritional status conilon coffee using the Balance Nutritional Index (BNI) and its relationship with productivity. The combination of precision agriculture and Recommendation Integrat